2018
DOI: 10.1364/josab.35.003049
|View full text |Cite
|
Sign up to set email alerts
|

Optical focusing based on the planar metasurface reflector with application to trapping cold molecules

Abstract: We demonstrate theoretically a 2D subwavelength silicon-grating reflector with strong focusing capability and the potential application to an optical dipole trap of cold molecules such as MgF. We study the dependence of the focusing properties of this reflector on its structural parameters, numerical aperture, and fabrication-error tolerance. Our study shows that the reflector delivers high reflectivity and strong focusing performances with the maximum intensity at the focal point over 200 times the incident o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…In the past, our group proposed the planar silicon grating with the focusing phase, and studied the dependence of the focusing properties on its structural parameters. We found that the focusing effect is impressive-with the maximum intensity at the focal point over 200 times than that obtained at the same point in the absence of the planar silicon grating [31]. Herein, we present a new scheme for generating a FHB on the subwavelength silicon-grating metasurface with a potential application as an optical dipole trap for cold molecules.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the past, our group proposed the planar silicon grating with the focusing phase, and studied the dependence of the focusing properties on its structural parameters. We found that the focusing effect is impressive-with the maximum intensity at the focal point over 200 times than that obtained at the same point in the absence of the planar silicon grating [31]. Herein, we present a new scheme for generating a FHB on the subwavelength silicon-grating metasurface with a potential application as an optical dipole trap for cold molecules.…”
Section: Introductionmentioning
confidence: 93%
“…In order to generate the FHB, the hybrid phase of the grating is designed to have focusing and completely destructive interference functions. From recent research, we studied the subwavelength silicon metasurface grating with the strong focusing capability [31]. Here, we used the phase distribution of the focusing lens in figure 2(a) to converge the light to one point, then combine the phase of figure 2(a) with an π-phase plate, which is a ring in figure 2(b) with an inner radius a (grey area) and an outer radius R (white area).…”
Section: Phase Distribution Of the Gratingmentioning
confidence: 99%
“…Since a phase-transmitting-type metasurface is nearly two-dimensional and the thickness d is generally kept unchanged in the manufacturing process, the phase accumulation φ is realized by changing the effective refractive index n eff at different positions. [20,22] Change in n eff is generally achieved by constructing a material microstructure of a higher refractive index on a substrate of a lower refractive index.…”
Section: Design Of the Metasurface Structural Elementmentioning
confidence: 99%
“…In contrast, an all-optical storage ring of cold molecules does not require the molecule to possess a permanent electric or magnetic dipole moment but induces an electric dipole moment to generate gradient forces to confine molecules into a potential trap. [20,22] Moreover, it is naturally immune to Majorana-type spin flips, which lead to the loss of trapped molecules. Therefore, the optical storage ring could have a broader range of applications.…”
Section: Monte-carlo Simulation Of Optical Storage Ringsmentioning
confidence: 99%
See 1 more Smart Citation